Catastrophic health care expenditure among older people with non-communicable diseases in 11 European Union Member States - Seda Kutluer; Milena Pavlova; Wim Groot (PLoS ONE, 2026)
Background Out-of-pocket payments by patients with chronic diseases can result in catastrophic expenditures. This study examines how chronic disease burden, measured by the presence of any chronic condition such as diabetes, cancer, chronic lung disease, heart attack, stroke and high blood pressure and the number of chronic conditions are associated with the likelihood of catastrophic out-of-pocket payments among older adults in 11 European Union (EU) countries. Methods The 2017 wave of the SHARE (Survey of Health, Ageing and Retirement in Europe) provides the most recent dataset suitable for our analysis. The sample size was 13,437. Probit regression models were estimated at 10%, 25% and 40% catastrophic health expenditure thresholds, controlling for demographic, socioeconomic and lifestyle characteristics, with standard errors clustered at the country level. Results Our findings show that the number of chronic conditions was statistically significant association with catastrophic health expenditures across all thresholds, whereas the presence of any chronic condition was significant only at the 10% threshold and not at higher thresholds. Compared to older people in Spain, which country has the lowest level of catastrophic out-of-pocket health expenditures in the EU, older people in the Czech Republic, Greece, Italy and Poland more frequently experienced catastrophic health expenditure, whereas older people in Austria, Germany, Sweden, France, and Denmark exhibited lower risks. Discussion Our findings demonstrate that multimorbidity, rather than the presence of a single chronic condition, drives catastrophic health expenditures among older adults. Older adults in the Czech Republic, Greece, Italy and Poland are more likely to experience catastrophic health expenditures compared to those in Spain, where out-of-pocket health expenditures are the lowest in the EU.